Study on spontaneous combustion characteristics of coal under thermo mechanical coupling - Ji Wu; Zongxiang Li; Shuoran Huang; Cong Ding (Scientific Reports)
Abstract The increase of coal seam mining depth leads to the increase of ground temperature stress, which affects the fracture development and spontaneous combustion characteristics of coal samples. Taking anthracite as the research object, scanning electron microscopy, low-temperature N2 adsorption, temperature- programmed experiments and infrared spectroscopy tests were carried out to analyze the mechanism of the influence of pore structure and the number of oxygen-containing functional groups on the spontaneous combustion characteristics of coal samples from the physical and chemical perspectives. The results show that the connection between pores and fractures is enhanced and the scale of micro-fractures is also increased after the thermal and mechanical coupling. After treatment, the oxidation of the coal sample was enhanced, and the overall production rate of the three iconic gases increased. The thermal and mechanical coupling results in the increase of the content of aromatic hydrocarbon, oxygen-containing functional group and aliphatic hydrocarbon in coal. The thermal and mechanical coupling effects promote the occurrence and development of coal spontaneous combustion by changing the structure, temperature and stress state of coal and affecting the reaction process of coal and oxygen. The research results have laid a theoretical foundation for the prevention and control of multi-field coupling CSC.